VALORISATION DES PROPRIETES ADSORBANTES D’UNE ARGILE, EXTRAITE DU GISEMENT DE M’ZILA (MOSTAGANEM), DANS LE DOMAINE DE LA DECOLORATION DES EFFLUENTS DE L’INDUSTRIE TEXTILE - LAHMAR, SARRA (My University, 2018)
In this study we evaluated the removal ability of purified clay modified with anionic dye Acid Green. The natural clay used which comes from the Mostaganem deposit, was treated with hydrochloric acid solution and then exchanged with sodium. Sodium clay obtained by sedimentation is modified by insertion between its layers an organic hexadecyltrimethylammonium species (HDTMA). The treatment of solutions containing 0.2 mmol L-1 of ACID GREEN has shown that the removal capacity of the organophilic clay is about 0.15 mmol g-1.